2017
DOI: 10.1182/bloodadvances.2016003921
|View full text |Cite
|
Sign up to set email alerts
|

A novel CXCR4 antagonist IgG1 antibody (PF-06747143) for the treatment of hematologic malignancies

Abstract: Key Points PF-06747143, a novel CXCR4 antagonist IgG1 Ab, mobilizes malignant cells from the BM and induces their death via Fc-effector function. PF-06747143 reduces tumor burden in NHL, AML, and MM models, both as a monotherapy or in combination with standard-of-care agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…High CXCR4 expression is also an independent risk factor for total survival time in patients with AML [114]. Finally, in multiple myeloma (MM) cells, CXCR4 expression correlated with disease progression [115], chemotherapy resistant MRD [116], and poor prognosis [117], while an increase in the CXCL12 serum expression level was associated with increased osteolytic disease and increased BM angiogenesis [118].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
See 1 more Smart Citation
“…High CXCR4 expression is also an independent risk factor for total survival time in patients with AML [114]. Finally, in multiple myeloma (MM) cells, CXCR4 expression correlated with disease progression [115], chemotherapy resistant MRD [116], and poor prognosis [117], while an increase in the CXCL12 serum expression level was associated with increased osteolytic disease and increased BM angiogenesis [118].…”
Section: Cxcl12/cxcr4 Axis In Hematological Tumors: a Crucial Hub Formentioning
confidence: 99%
“…A phase 3 trial (NCT03246529) is currently evaluating the use of motixafortide for stem cell mobilization [167]. Actually, there are two fully human anti-CXCR4 antibodies-PF-06747143 [116] and ulocuplumab [168]-used for the treatment of hematologic malignancies. Finally, LY2510924, is a potent cyclic peptide antagonist of CXCR4 with acceptable in vivo stability and a pharmacokinetic profile similar to a typical small molecule inhibitor [169], which is being evaluated in phase 1/2 clinical trials in extensive small cell lung cancer (NCT01439568), renal cancer (NCT 01391130), and in association with durvalumab (an anti Programmed Death-Ligand 1 (PD-L1) in solid tumors (NCT02737072).…”
Section: Cxcr4 Targeting In Hematological Tumorsmentioning
confidence: 99%
“…LY2624587 is another anti-CXCR4 IgG4 antibody with similar mode of action, which has also reached the clinical trial phase (Table 2) (Peng et al, 2016b). The combination of CXCR4 inhibition, induction of apoptosis, and ADCC and CDC effector functions is employed in an IgG1 from Pfizer, PF-06747143, and shows a strong effect in multiple hematologic tumor models (Table 2) (Kashyap et al, 2017;Liu et al, 2017;Zhang et al, 2017). Utilization of different antibody formats and Fc engineering strategies provides an attractive flexibility in pursuing specific therapeutic needs.…”
Section: Targeting Cxcr4 and Ackr3 With Antibodiesmentioning
confidence: 99%
“…C-X-C motif chemokine receptor 4 (CXCR4) serves an important role in cell migration, with certain studies hypothesizing that cell migration is predominantly dependent on the CXCR4/stromal-derived factor-1 (SDF-1) axis (11). CXCR4 and its ligand SDF-1 are primarily studied for their crucial roles in the homing of stem and progenitor cells in the bone marrow, chemotaxis, cell arrest, angiogenesis, metastasis and cell survival (12). Tavor et al (13) reported that AML cells constitutively secrete and express SDF-1-dependent cell surface elastase, which regulates their migration and proliferation.…”
Section: Introductionmentioning
confidence: 99%